LL5 directs the translocation of Filamin A and SHIP2 to sites of phosphatidylinositol 3,4,5-triphosphate (PtdIns(3,4,5)P3) accumulation, and PtdIns(3,4,5)P3 localization is mutually modified by co-recruited SHIP2 - Takabayashi, Tetsuji; Xie, Min-Jue; Takeuchi, Seiji; Kawasaki, Motomi; Yagi, Hideshi; Okamoto, Masayuki; Rahman, Mohammad Tariqur; Malik, Fawzia; Kuroda, Kazuki; Kubota, Chikara; Fujieda, Shigeharu; Nagano, Takashi; et al. (American Society for Biochemistry and Molecular Biology Inc., 2010)
Phosphatidylinositol 3,4,5-triphosphate (PtdIns(3,4,5)P3) accumulates at the leading edge of migrating cells and works, at least partially, as both a compass to indicate directionality and a hub for subsequent intracellular events. However, how PtdIns(3,4,5)P3 regulates the migratory machinery has not been fully elucidated. Here, we demonstrate a novel mechanism for efficient lamellipodium formation that depends on PtdIns(3,4,5)P3 and the reciprocal regulation of PtdIns(3,4,5)P3 itself. LL5β, whose subcellular localization is directed by membrane PtdIns(3,4,5)P3, recruits the actin-cross-linking protein Filamin A to the plasma membrane, where PtdIns(3,4,5)P3 accumulates, with the Filamin A-binding Src homology 2 domain-containing inositol polyphosphate 5-phosphatase 2 (SHIP2). A large and dynamic lamellipodium was formed in the presence of Filamin A and LL5β by the application of epidermal growth factor. Conversely, depletion of either Filamin A or LL5β or the overexpression of either an F-actin-cross-linking mutant of Filamin A or a mutant of LL5β without its PtdIns(3,4,5)P3-interacting region inhibited such events in COS-7 cells. Because F-actin initially polymerizes near the plasma membrane, it is likely that membrane-recruited Filamin A efficiently cross-links newly polymerized F-actin, leading to enhanced lamellipodium formation at the site of PtdIns(3,4,5)P3 accumulation. Moreover, we demonstrate that co-recruited SHIP2 dephosphorylates PtdIns(3,4,5)P3 at the same location.